About Lanthanoid Fluoride Selenide Oxoselenotantalates with the Composition Ln3F2Se2TaO4 (Ln = La – Nd). Issue 18 (30th September 2020) - Grossholz, Hagen; Buyer, Constantin; Lotter, Sebastian M. A.; Wolf, Sarah; Schleid, Thomas
Abstract : After solid‐state reactions of the light lanthanoid metals, their oxides and fluorides as well as selenium in sealed tantalum ampoules with sodium chloride as a fluxing agent at 850 °C for 8 days needle‐shaped single crystals of Ln 3 F2 Se2 TaO4 ( Ln = La – Nd) were obtained. They crystallize in the orthorhombic space group Pnma analogous to La3 F2 Se2 NbO4 with a = 1133–1120 pm, b = 400–393 pm and c = 1812–1778 pm ( Ln = La – Nd) for Z = 4 as the first known quinary lanthanoid(III) oxoselenotantalates(V) with fluoride and selenide anions. The three crystallographically different Ln 3+ cations are all surrounded by nine anions (O 2–, F – and Se 2– ) each. Tantalum resides in an octahedral chalcogen coordination by forming trans ‐vertex oxygen‐connected [TaO5 Se] 7– polyhedra, which build up chains 1 ∞ [TaO V 2/2 O t 3/1 Se t 1/1 ] 5– along [010]. The sites of the four crystallographically different oxygen atoms and the two distinct fluoride anions were established by bond‐valence calculations. One fluorine and three oxygen atoms are surrounded tetrahedrally by cations, while another fluoride and oxide anion exhibit just triangular non‐planar coordination spheres. The two independent Se 2– anions have five or six cationic neighbors. Abstract :